Association of Dilated Cardiomyopathy with the Striatin Mutation Genotype in Boxer Dogs. (28th August 2013) - Meurs, K.M.; Stern, J.A.; Sisson, D.D.; Kittleson, M.D.; Cunningham, S.M.; Ames, M.K.; Atkins, C.E.; DeFrancesco, T.; Hodge, T.E.; Keene, B.W.; Reina Doreste, Y.; Leuthy, M.; et al.
<x xml:space="preserve">Abstract</x> Background Myocardial disease in the Boxer dog is characterized by 1 of 2 clinical presentations, dilated cardiomyopathy (DCM) characterized by ventricular systolic dysfunction, dilatation and tachyarrhythmias, and arrhythmogenic right ventricular cardiomyopathy (ARVC) characterized by ventricular tachyarrhythmias, syncope, and sudden death. Boxer ARVC has been associated with a deletion in the striatin gene in some families. Hypothesis/Objectives We hypothesized that both presentations represent a single disease, and the development of DCM in the Boxer is associated with the striatin deletion. Animals Thirty‐three adult Boxer dogs with DCM, 29 adult Boxer dogs with the striatin deletion and ARVC, and 16 Boxers without cardiac disease. Methods DNA samples were evaluated for the striatin deletion. Association of the deletion with the DCM phenotype was tested by a Fisher's exact test. T‐tests were used to evaluate potential differences between the positive heterozygous and positive homozygous groups with DCM with regard to age, LVIDD, LVIDS, and FS%. Results Thirty of 33 dogs with DCM were positive for the striatin deletion. The striatin mutation and the homozygous genotype were strongly associated with the DCM phenotype (P < .001 and P = .005). There was no statistical difference between the heterozygous and homozygous groups with regard to age and echocardiographic measurements. Conclusions and Clinical Importance This study demonstrates an association between DCM in the Boxer dog and the striatin mutation, particularly with the homozygous genotype. The observation that 3/33 dogs developed DCM and lacked the striatin mutation suggests that there is at least 1 other cause of DCM in the Boxer dog.